Incentives or disincentives? Intellectual property protection and FinTech innovation - Evidence from Chinese cities - Ding, Lei; Xue, Peng (Finance research letters, 2023)
•Intellectual property rights protection found to significantly boost FinTech innovation.•Stronger intellectual property laws can catalyse R&D investment in the FinTech sector.•Calls for increased intellectual property education and a supportive innovation ecosystem. This study investigates the impact of intellectual property rights protection (IPRP) on FinTech innovation. Using panel data from 284 prefecture-level cities in China between 2013 and 2020, panel models and 2SLS estimation are employed to examine the relationship between IPRP and FinTech innovation. The results demonstrate that IPRP serves as an effective incentive for driving FinTech innovation. This finding remains robust even after addressing endogeneity and conducting various robustness tests. By shedding light on the influence of IPRP on FinTech innovation, particularly in the context of business model innovation, this study contributes to an improved understanding of the subject.